1996
DOI: 10.1007/bf00223378
|View full text |Cite
|
Sign up to set email alerts
|

Advanced backcross QTL analysis in a cross between an elite processing line of tomato and its wild relative L. pimpinellifolium

Abstract: Approximately 170 BC2 plants from a cross between an elite processing inbred (recurrent parent) and the wild species Lycopersicon pimpinellifolium LA1589 (donor parent) were analyzed with segregating molecular markers covering the entire tomato genome. Marker data were used to identify QTLs controlling a battery of horticultural traits measured on BC2F1 and BC3 families derived from the BC2 individuals. Despite its overall inferior appearance, L. pimpinellifolium was shown to possess QTL alleles capable of enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 358 publications
(135 citation statements)
references
References 12 publications
6
128
0
1
Order By: Relevance
“…Genetic resources promise to contribute favorable alleles to breeding programs, even if their performance with respect to the trait under consideration is worse than that of elite breeding material (Tanksley et al, 1996;Xiao et al, 1998;McCouch 2004;Falke et al, 2009b). NIL libraries provide the possibility of detecting such favorable QTL alleles as experimentally shown for plant height in rye (Falke et al, 2009b).…”
Section: Additional Quantitative Genetic Scenariosmentioning
confidence: 99%
“…Genetic resources promise to contribute favorable alleles to breeding programs, even if their performance with respect to the trait under consideration is worse than that of elite breeding material (Tanksley et al, 1996;Xiao et al, 1998;McCouch 2004;Falke et al, 2009b). NIL libraries provide the possibility of detecting such favorable QTL alleles as experimentally shown for plant height in rye (Falke et al, 2009b).…”
Section: Additional Quantitative Genetic Scenariosmentioning
confidence: 99%
“…A previous study had examined the genetic control of domestication traits in the same population (Doganlar et al 2002b). The use of interspecific F 2 and advanced backcross populations has proven to be an effective and efficient way of mapping agronomic and horticultural traits in eggplant's relatives: tomato, potato and pepper (e.g., Bonierbale et al 1994;Tanksley et al 1996;Ben Chaim et al 2001). In addition to providing adequate phenotypic and DNA polymorphism which may be limiting in intraspecific eggplant populations (Nunome et al 2001), interspecific populations can supply the starting material for the introgression of valuable traits from wild species into eggplant cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Recombination was lower at chromosome 2 and higher at chromosomes 1, 6, 7, 9, 11 and 12. Fragmentation of the introgressed segments after some selfing or backcross generations has been also demonstrated by Eshed et al (1992) and Tanksley et al (1996) respectively. Fulton et al (1997) also found the progressive decrease of the size of the introgressed fragments of S. peruvianum in S. lycopersicum.…”
Section: Discussionmentioning
confidence: 92%